Diversity management: Challenges, benefits, and the role of human resource management in Brazilian organizations - Jabbour, Charbel Jose Chiappetta; Gordono, Fernanda Serotini [UNESP]; Oliveira, Jorge Henrique Caldeira De; Martinez, Jose Carlos [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP] (Emerald, 2011)
Purpose The objective of this study was to analyze the major challenges and benefits of diversity management in Brazilian companies by assessing the role of human resources. Design/methodology/approach A total of 15 case studies were carried out on companies that operate in Brazil. Brazil is a country with considerable diversity and multiracial backgrounds. Findings It was found that diversity management in Brazilian companies is still an emerging issue, and the major challenges are related to discriminatory actions taken by coworkers. Among the 15 companies studied, only four had adopted a consistent set of diversity management and human resources practices. These four companies were the only companies to affirm that diversity management requires the strong support of top management and continuous organization to sustain efforts toward incorporating diversity. Originality/value Research studies on diversity management in Brazil are scarce. The findings of this study, however, can be useful to academic professionals and company directors in countries that exhibit similar characteristics to those of Brazil, or to those who are interested in learning more about Brazil. © 2011 Emerald Group Publishing Limited. All rights reserved.
Keywords: Brazil; Equal opportunities; Human resource management